Perlindungan Hukum Konsumen atas Informasi Harga pada Produk Minuman - M Syahrul Bahri; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Drinking is one of the main needs of humans in the world that must be fulfilled for activity. Every human being must meet his needs, especially drinks, whether in quantity or in terms of the health of the drink. Therefore, the State must provide security for its people without exception whether it is related to supervision or regulating its circulation. This study aims to explain the legal protection for consumers for information on the price of beverage products listed on the packaging and to explain the resolution efforts regarding the difference between the price on the packaging and the selling price paid. This research used normative legal research, with a juridical approach through the hermenutic method. The data used were secondary and primary data which were analyzed qualitatively. The result of the research showed that the government has provided consumer protection for the provision of accurate information by means of obligations imposed by business actors as well as prohibitions that cannot be violated. The responsibility of business actors to resolve disputes can be pursued through channels outside the court as well as through court channels. The factors that influence the occurrence of a product that is nominally different from the price on the packaging consist of internal factors and external factors. If there is a difference in price on the package and at the time of payment, the cheapest fee will be paid.